Development and Evaluation of MilleaLab-Based Virtual Reality Media for Learning Plant Anatomy, Cell Biology, and the Nervous System - Dea Diella; Ryan Ardiansyah; Egi Nuryadin (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2026)
Student engagement in biology learning remains a significant challenge, particularly when students are required to understand abstract concepts such as plant anatomy, cell biology, and the nervous system. Virtual Reality (VR) offers immersive and interactive learning environment that has potential to enhance students’ learning experiences and engagement. This study aimed to develop and evaluate MilleaLab-based Virtual Reality learning media for teaching plant anatomy, cell biology, and the nervous system. The study employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The feasibility of the developed media was assessed by subject matter expert and VR media expert using validation sheets, while student engagement was measured through a student engagement questionnaire. The result indicated that the VR-based learning media achieved feasibility scores above 80%, demonstrating that the media is highly feasible for biology learning. Furthermore, the findings revealed that the VR media contributed positively to students’ behavioral and psychological engagement, with average score above 3.0, while cognitive engagement showed a lower average score below 3.0. These findings suggests that MilleaLab-based VR media can serve as innovative learning alternative for teaching complex biology concepts by promoting active participation and positive learning experiences among students.